475 Increasing Writing Self-Efficacy in Early-Career Researchers from Underrepresented Backgrounds: A Pilot Study. (April 2022) - Mayowski, Colleen A.; Rubio, Doris M.; Proulx, Chelsea N.
Abstract : OBJECTIVES/GOALS: Writers with high self-efficacy perform better than writers with low self-efficacy regardless of writing ability. We investigated whether Shut Up & WriteÂ® (SUAW), a less-intensive writing intervention, produced gains in writing self-efficacy similar to those reported by intensive, longer-term interventions. METHODS/STUDY POPULATION: Meetings were held 2x/wk for 5 wks via Zoom, for 1 hour. Participants were encouraged to attend at least 1x/wk. The 1st few mins were devoted to a discussion of what each person planned to work on. Then, a timer was set and each writer muted themselves, shuttered their webcam, and wrote. When the alarm sounded, everyone returned to the group, and discussed what was accomplished. We measured writing self-efficacy before & after participating in SUAW using a pre-post survey design and used two-tailed paired t-tests to test for significant differences between pre- and post-test means. SUAW participants (n=23) were in 1 of 2 categories: 10 were self-selected LEADS scholars from MSIs, and 13 were medical students in a palliative care program. 86% were URB, 78% were female. RESULTS/ANTICIPATED RESULTS: Seven (30%) SUAW participants completed both the pre- and post-survey. Individuals showed significantly higher agreement from pre-to-post on the self-efficacy item "I have a generally positive attitude toward writing" (p=0.047) using a 5-point Likert scale from "completely agree" to "completely disagree." Most other items did not indicate significant change between pre- and post-survey. The mean of the question "How satisfied were you with this Shut Up & Write activity?" which appeared only on the post-survey (n=10) was 1.10 (1=extremely satisfied, 5=extremely dissatisfied). Anticipated result: We suspect that the benefits of SUAW are best actualized by ongoing attendance, and that benefits are cumulative. DISCUSSION/SIGNIFICANCE: We found that participation in SUAW promotes writing self-efficacy in early-career URB researchers. This is an exciting finding because publishing ones research is essential for academic advancement, and research supports a relationship between writing self-efficacy and writing production. This may curtail URB scientists' rate of attrition.